Application of Age, Body Mass Index, Chronic Kidney Disease, Diabetes, and Genotyping Score for Efficacy of Clopidogrel: Secondary Analysis of the CHANCE Trial. Issue 2 (February 2022) - Dai, Liye; Xu, Jie; Yan, Hongyi; Chen, Zimo; Pan, Yuesong; Meng, Xia; Li, Hao; Wang, Yongjun
Abstract : Background and Purpose: The age, body mass index, chronic kidney disease, diabetes, and genotyping (ABCD-GENE) score is a validated risk score integrating CYP2C19 genotypes with clinical risk factors influencing clopidogrel response that would allow the more precise identification of subjects at risk for high platelet reactivity and adverse clinical outcomes. Our objective was to further verify application of the ABCD-GENE score and investigate appropriate cutoff value in patients with minor stroke or transient ischemic attack. Methods: In this post-analysis of the CHANCE trial (Clopidogrel in High-Risk Patients With Acute Nondisabling Cerebrovascular Events), the ABCD-GENE score was calculated for all patients enrolled in this study. By using the proposed cutoff of 10, patients were stratified as being at high risk for high platelet reactivity or not. We further categorized the ABCD-GENE score to 0 to 5, 6 to 24, and >24 to investigate the cutoff value of this scale in clinical application. Stroke recurrence at 3 months was considered as the primary outcome. Results: Among a total of 2923 patients with minor stroke/transient ischemic attack, there were 2273 (77.76%) with ABCD-GENE score <10 and 650 (22.24%) patients with ABCD-GENE score ≥10. Compared with the aspirin alone, hazard ratios (95% CIs) of the clopidogrel-aspirin therapy for stroke recurrence were 0.70 (0.54–0.91) and 0.76 (0.46–1.24), among patients of ABCD-GENE scores <10 and ABCD-GENE scores ≥10, respectively. Stratified analyses by ABCD-GENE score 0 to 5, 6 to 24, and >24, hazard ratios of the clopidogrel-aspirin therapy for stroke recurrence were 0.57 (95% CI, 0.38–0.85), 0.78 (0.58–1.06), and 1.20 (0.44–3.28) ( P value for trend=0.0052). Conclusions: Among Chinese minor stroke/transient ischemic attack population, the efficacy of clopidogrel-aspirin therapy was decreased in patients with higher ABCD-GENE score. Our study suggests that CYP2C19 genotypes and clinical risk factors can be integrated by ABCD-GENE score to estimate the efficacy of clopidogrel-aspirin therapy. Abstract : Supplemental Digital Content is available in the text.